Aerosol Optical Properties of a Haze Episode in Wuhan Based on Ground-Based and Satellite Observations - Miao Zhang; Yingying Ma; Wei Gong; Zhongmin Zhu (Atmosphere, 2014)
A severe haze episode that occurred in Wuhan, central China, from 6–14 June 2012 was investigated using ground-based and satellite-derived observations, from which the optical properties and vertical distribution of the aerosols were obtained. The mass concentrations of PM2.5 and black carbon (BC) were 9.9 (332.79 versus 33.66 μg∙m−3) and 3.2 times (9.67 versus 2.99 μg∙m−3) greater, respectively, on haze days than during normal weather. The large aerosol loading contributed to the high values of the scattering (2.32 km−1) and absorption coefficients (0.086 km−1). Particle size became larger, consistent with the reduced scattering Ångström exponent. The high asymmetry parameter (0.65) and single scattering albedo (SSA) (0.97) observed in the haze, which coincided with the relatively low backscatter ratio (0.11) and up-scatter fraction (0.23), were related to the increased particle size, and could have had a heating effect on the atmosphere. Aerosols accumulated primarily below 3 km and according to CALIPSO, were regular in their shapes. At the surface, the aerosol extinction coefficient detected by satellite remained at ~1 km−1, very close to the ground-based observations. Aerosol optical properties measured at this downtown site could help further the understanding of the effects of aerosols on the air quality, city environment, and radiation balance.